Analisis Efektivitas dan Efisiensi Pendapatan dan Belanja pada Anggaran Pendapatan dan Belanja Desa Kampung Baru Kecamatan Maro Sebo Ulu - Sri Rosmawati; Afriantoni Afriantoni (CITRA EKONOMI, 2022)
Regional autonomy is the right, authority and obligation of autonomous regions to regulate and take care of their own government affairs and the interests of local communities in accordance with laws and regulations. The village is the lowest autonomous region, so the village is the object of the fiscal decentralization system that comes from the central government and local government. As a report on the responsibility of the Village government to the funds it manages, the Village Revenue and Expenditure Budget needs to be analyzed whether the income obtained has been spent according to planning. For this reason, effectiveness and efficiency measurements of income and expenditure are carried out in the Village Revenue and Expenditure Budget. This study aims to analyze the effectiveness and efficiency of the Revenue and Expenditure Budget of Kampung Baru Village, Maro Sebo Ulu District for the 2019 and 2020 fiscal years. The results of the discussion showed that the effectiveness of the Kampung Baru Village APB in 2019 was Effective and in 2020 it was quite effective. While the efficiency of the Kampung Baru Village APB in 2019 and 2020 is quite efficient.